2022
DOI: 10.1093/eurheartj/ehac544.1401
|View full text |Cite
|
Sign up to set email alerts
|

Infarct size, inflammatory burden and admission hyperglycemia in diabetic patients with acute myocardial infarction treated with SGLT2-inhibitors: a multicenter international registry

Abstract: Background Sodium-glucose co-transporter 2 inhibitors (SGLT2-I) currently receive intense clinical interest in patients with and without diabetes mellitus (DM) with pleiotropic beneficial effects. Nowadays, the inflammation response in the setting of acute myocardial infarction (AMI) has been proposed as a potential pharmacological intervention target. In this setting, we tested the hypothesis that the SGLT2-I displays anti-inflammatory effect along with glucose-lowering properties. We invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Studies have shown that excessive alcohol consumption can cause heart failure and irreversible damage to the heart muscle. Once alcoholic cardiomyopathy occurs, besides causing severe heart failure, it can cause serious arrhythmias, which pose a serious threat to human health and have become urgent concerns [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that excessive alcohol consumption can cause heart failure and irreversible damage to the heart muscle. Once alcoholic cardiomyopathy occurs, besides causing severe heart failure, it can cause serious arrhythmias, which pose a serious threat to human health and have become urgent concerns [ 21 ].…”
Section: Introductionmentioning
confidence: 99%